2017
DOI: 10.17140/pcsoj-3-127
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Study on the Effects of a Documentary on Students’ Empathy and Attitudes towards Older Adults

Abstract: Background Despite the rapid increase in the size of the geriatric population, no current published literature is available based on the effects of viewing a documentary covering medical and psychosocial issues concerning older adults influencing young people’s empathy and ageism. The aim of the current study was to test whether participants who viewed an original documentary about older adults experiencing physical pain would report lower ageism and higher empathy scores when compared to participants who watc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Various social projects can be implemented for this purpose, for example, "friendly visitor" types of programs in which young people visit the elderly [51,52], but also mass media, including films, which have a high potential for impact [53,54]. It was found that watching documentary films had a positive effect on both knowledge about aging and attitudes towards the elderly [55]; these films significantly improved empathy towards elderly people among university students [56].…”
Section: Introductionmentioning
confidence: 99%
“…Various social projects can be implemented for this purpose, for example, "friendly visitor" types of programs in which young people visit the elderly [51,52], but also mass media, including films, which have a high potential for impact [53,54]. It was found that watching documentary films had a positive effect on both knowledge about aging and attitudes towards the elderly [55]; these films significantly improved empathy towards elderly people among university students [56].…”
Section: Introductionmentioning
confidence: 99%
“…[24,31] Because, empathictendency is a vital element in all activities of nursing and is thebasic element of human-oriented holistic and humanistic nursing care. [32,33]…”
Section: Discussionmentioning
confidence: 99%
“…This might be surprising at first glance, in light of findings that social network size and social contacts diminish in older age [49,50] and based on prior evidence demonstrating negative attitudes towards older adults ('ageism') [51,52] . The latter has been argued to lead to reduced empathy towards older adults [53,54] . However, in line with what we observed here, previous cross-sectional and longitudinal studies have shown that older age was not associated with a decline in social connectedness per se [55,56] .…”
Section: Discussionmentioning
confidence: 99%